2017
DOI: 10.4314/thrb.v19i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and precipitating factors of diabetic ketoacidosis among patients admitted to intensive care unit at a tertiary hospital in Mwanza, Tanzania

Abstract: Background: Diabetic ketoacidosis (DKA), one of the common emergencies in patient with diabetes mellitus is associated with considerable morbidity and mortality. This study aimed to determine clinical presentation and precipitating factors of DKA among patients admitted at Bugando Medical Centre (BMC) in north-western Tanzania. Methods: This study involved a retrospective review of hospital records of DKA patients admitted to intensive care unit at BMC during 2012. Data on demographics, precipitating factors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 14 publications
0
13
2
Order By: Relevance
“…But in the current study, it was more prevalent due to different reasons. 23,24 The most common precipitating factors for DKA in this study were non-adherence to insulin treatment and infection. 23,25 Pneumonia was identified as the major concurrent infection.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…But in the current study, it was more prevalent due to different reasons. 23,24 The most common precipitating factors for DKA in this study were non-adherence to insulin treatment and infection. 23,25 Pneumonia was identified as the major concurrent infection.…”
Section: Discussionmentioning
confidence: 75%
“…Thus, the higher in-hospital mortality rate in our setting and other parts of the world is the issue that needs urgent attention to improve the quality of DKA care. 12 , 24 , 25 , 30 - 32 The most probable reason for such a high mortality rate could be due to lack of appropriate diabetic care, lack of screening for hypoglycemia and hypokalemia, financial constraints for laboratory support and insulin, as well as poor management practice of co-morbidity treatment like hypokalemia and hypoglycemia. 27 - 29 Therefore, in developing countries like Ethiopia, there should be free health care for those patients with DM to improve access to quality care.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, continuous education remains key and utilising opportunities during clinical reviews to ensure patients know about the importance of sugar control by adhering to their medications and prevention of complications. A study in a neighboring country; Tanzania, showed similar results of a higher number (72.4%) of DKA patients being already diagnosed DM patients (Iddi et al, 2017).…”
Section: Discussionmentioning
confidence: 66%
“…1,[3][4][5][6][7] It is one of the common emergencies among patients with diabetes mellitus and is associated with considerable morbidity and mortality. 8 It is still the leading cause of death; and mortality risk is substantially increased in patients with chronically poor glycemic control and frequent DKA. 3 Frequent DKA is a serious and common health problem.…”
Section: Introductionmentioning
confidence: 99%
“…10 In Africa, the mortality rate due to DKA is unacceptably higher. 8 In developing countries, it ranges from 6% to 24%. In Ethiopia, the risk of dying from DKA is higher due to poor medical services in the country.…”
Section: Introductionmentioning
confidence: 99%